Institutional transformation of S&T systems in the European economies in transition: Comparative analysis - Werner Meske (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1998)
In all Central and East European Countries (CEEC) the first phase of transformation comprised the dissolution and fragmentation of the socialist S&T system through top-down and bottom-up processes, and was linked to S&T personnel being cutback to approximately 20 to 50% of the former peak level. Subsequent to this the restructuring of S&T performing institutions and their 'environments' in politics and economy commenced. In this second phase the progress made by the CEEC in their institutional transformation has varied: A group of advanced countries (I) consists of Poland, the Czech Republic, Hungary, Estonia and Slovenia. With the restructuring of S&T organisations and activities they have substantially completed the second phase of transformation. They are now faced with the task of creating a modern S&T system by interlinking the newly formed actors in science, the economy and politics (Phase 3). Countries of the Group II have introduced institutional changes through new bodies, laws, competitive R&D funding, etc. but have not yet fully implemented them in practice due to instability in the economy. A third group of countries has established a stable framework for S&T neither in the economy (continuing decline in GDP) nor in politics. Typical problems faced by all countries undergoing transformation are the disproportions between 'academic' science and weak industrial R&D, the increase in the percentage of older scientists, in particular in the natural sciences and technical disciplines, and the underdeveloped infrastructure in S&T. This situation leads to differences in the future of S&T systems as well as in the main focus of S&T policy in the individual CEEC, which ranges from continual restructuring to international integration. – – In allen mittel- und osteuropäischen Ländern (MOEL) bestand die erste Phase der Transformation in der Auflösung und Fragmentierung des sozialistischen Wissenschafts- und Techniksystems (WuT) durch top-down- und bottom-up-Prozesse. Diese Phase war verbunden mit einer Reduzierung des Personals in WuT auf etwa 50 bis 20 Prozent des früheren höchsten Bestandes. Anschließend erfolgte die Umgestaltung der WuTdurchführenden Institutionen und ihrer Umwelten in Politik und Wirtschaft. In dieser zweiten Phase gab es unterschiedliche Fortschritte in bei der institutionellen Transformation: Eine Gruppe von fortgeschrittenen Ländern (I), zu der Polen, die Tschechische Republik, Ungarn, Estland und Slowenien gehören, hat mit der Umgestaltung ihrer WuT-Einrichtungen und -Aktivitäten im wesentlichen die zweite Phase der Transformation durchlaufen. Diese Länder stehen nun vor der Aufgabe, ein modernes WuT-System durch Vernetzung der neugeschaffenen Akteure in Wissenschaft, Wirtschaft und Politik zu schaffen (Phase 3). Länder der Gruppe II haben ebenfalls institutionelle Veränderungen in Form neuer Gremien, Gesetze, wettbewerblicher FuE-Finanzierung usw. eingeführt, aber wegen einer instabilen Wirtschaft noch nicht voll in der Praxis durchgesetzt. Eine dritte Gruppe von Ländern hat weder in der Wirtschaft (anhaltender Rückgang des BIP) noch in der Politik stabile Rahmenbedingungen für WuT geschaffen. Typische Probleme, vor denen alle Transformationsländer stehen, sind die Disproportionen zwischen akademischer Wissenschaft und der schwachen industriellen FuE, das Anwachsen des Anteils von älteren Wissenschaftlern, insbesondere in den Natur- und Technikwissenschaften, sowie die unterentwickelte Infrastruktur in WuT. Diese Situation führt zu Unterschieden in der Zukunft der WuT-Systeme, aber auch bei den Schwerpunkten der WuT-Politik in den individuellen MOEL, die von anhaltender Umgestaltung bis zu Aufgaben der internationalen Integration reichen.
Keywords: 300; Wissenschaft; Forschung; Institutioneller Wandel; Übergangswirtschaft; Osteuropa